Geotechnical evaluation of loess modifications as the sustainable compacted soil liner material in solid waste landfill - Zhengrui Zhang; Siti Jahara Matlan; Hao Wang; Ahad Amini Pishro; Lili Zhang; Xian Gao; Zhao Liang; Xiaoyi Liu; Peigen Zhao (MDPI, 2022)
This paper studied the anti-seepage ability of the modified loess by using attapulgite, which is abundant in local areas. The possibility of using the modified loess as the sustainable compacted soil liner material in a solid waste landfill was also considered in this research. The materials were then evaluated using Nuclear Magnetic Resonance (NMR), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), and an Impermeability Mechanism (IM). The experimental results showed that the permeability coefficient of the attapulgite-modified loess decreases significantly with increasing attapulgite content. However, it becomes less significant when the attapulgite level approaches 10%. Both cases can meet the landfill impermeability requirements, based on the attapulgite content remaining at 10%, adding 15% lime or 5% cement, respectively. The triaxial consolidation and drainage experiment was carried out to investigate the shear strength of the materials under three different working circumstances. The stress–strain curves of each specimen were produced, as were the cohesion and internal friction angle values. This research lays the groundwork for using attapulgite-modified loess as a landfill lining material. It establishes a solid platform for future studies on attapulgite adsorption and purifying performance in landfills.